The sFlt-1/PlGF Ratio Trend Is Useful in Predicting Preeclampsia Severity in Hyperreactio Luteinalis Complicated with Preeclampsia - Risa Miyatake; Tatsuya Fujii; Keiichi Kumasawa; Mari Ichinose; Masatake Toshimitsu; Seisuke Sayama; Takahiro Seyama; Takayuki Iriyama; Takeshi Nagamatsu; Yutaka Osuga (Case Reports in Obstetrics and Gynecology)
Hyperreactio luteinalis (HL) is a rare condition that presents as bilateral ovarian enlargement during pregnancy. Typically, it is thought to be caused by increased production of human chorionic gonadotropin (hCG) associated with gestational trophoblastic diseases or multiple pregnancies. The prognosis is relatively good, with many cases resulting in term birth. However, some obstetric complications, such as preeclampsia (PE) and preterm births, have been reported. We present a serious case of HL with subsequent PE that resulted in preterm delivery at 31 weeks of gestation. The soluble fms-like tyrosine kinase-1 (sFlt-1)/placental growth factor (PlGF) ratio was very high at the onset of PE at 24 weeks of gestation, followed by a modest decline, which then increased in proportion to the exacerbation of symptoms. Since HL cases have also been reported to be associated with PE, repeated measurement of the sFlt-1/PlGF ratio proved useful for better pregnancy management.